A review on techno managerial approaches to energy optimization in chemical process industries - Parekh, Nishita; Kurian, Jinu; Patil, Rajesh; Gautam, Richa (Frontiers in Energy Research, 2023)
The chemical process industries, being energy intensive in nature, still struggle to strategically and sustainably consider energy management issues. Energy sustainability depends on a sustainable energy supply, consumption, and waste disposal. This paper analyses current energy management and optimization in industries and also attempts to identify the significance of incorporating energy management into the strategic perspectives of industry through an exhaustive literature review. To ensure the optimization of energy, the paper illustrates the importance of adopting a techno-managerial approach that integrates the technical aspects of energy conservation with relevant management tactics. This is also a preliminary study for proposing a framework for Indian chemical process SMEs to systematically overcome various challenges and seize the opportunity to ensure optimized energy utilization, thereby highlighting the framework’s long- and short-term benefits. The suggestions in the paper would help these industries and local- and national-level policymakers to improve their energy footprint and make the world more energy sustainable.